Decavanadate Toxicology and Pharmacological Activities: V-10 or V-1, Both or None? - Aureliano, M. (2017)
This review covers recent advances in the understanding of decavanadate toxicology and pharmacological applications. Toxicological in vivo studies point out that V-10 induces several changes in several oxidative stress parameters, different from the ones observed for vanadate (V-1). In in vitro studies with mitochondria, a particularly potent V-10 effect, in comparison with V-1, was observed in the mitochondrial depolarization (IC50 = 40 nM) and oxygen consumption (99 nM). It is suggested that mitochondrial membrane depolarization is a key event in decavanadate induction of necrotic cardiomyocytes death. Furthermore, only decavanadate species and not V-1 potently inhibited myosin ATPase activity stimulated by actin (IC50 = 0.75 mu M) whereas exhibiting lower inhibition activities for Ca2+-ATPase activity (15 mu M) and actin polymerization (17 mu M). Because both calcium pump and actin decavanadate interactions lead to its stabilization, it is likely that V-10 interacts at specific locations with these proteins that protect against hydrolysis but, on the other hand, it may induce V-10 reduction to oxidovanadium(IV). Putting it all together, it is suggested that the pharmacological applications of V-10 species and compounds whose mechanism of action is still to be clarified might involve besides V-10 and V-1 also vanadium(IV) species.